A Brief Review of Cuckoo Search Algorithm (CSA) Research Progression from 2010 to 2013 - Shair, Ezreen Farina; Khor, Shen Young; Abdullah, Abdul Rahim; Jaafar, Hazriq Izzuan; Mohd Ali, Nursabillilah; Zainal Abidin, Amar Faiz (Praise Worthy Prize, 2014)
Cuckoo Search Algorithm is a new swarm intelligence algorithm which based on breeding behavior of the Cuckoo bird. This paper gives a brief insight of the advancement of the Cuckoo Search Algorithm from 2010 to 2013. The first half of this paper presents the publication trend of Cuckoo Search Algorithm. The remaining of this paper briefly explains the contribution of the individual publication related to Cuckoo Search Algorithm. It is believed that this paper will greatly benefit the reader who needs a bird-eyes view of the Cuckoo Search Algorithm’s publications trend.